Pengaruh Green Marketing, Digital Engagement, Dan Citra Klinik Terhadap Kepuasan Pasien BPJS Di Klinik Utama Sudirjo Partodimejo Dalam Perspektif Pembangunan Berkelanjutan - Wahyu Ramadhani; Nurhidayah Nurhidayah; Ratna Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study is motivated by the importance of improving BPJS patient satisfaction as an indicator of sustainable healthcare service quality. Patient satisfaction is influenced not only by medical service quality but also by environmentally friendly practices, digital technology utilization, and the image of healthcare facilities. From the perspective of consumer behavior and service quality, green marketing, digital engagement, and clinic image are assumed to shape patient satisfaction, with sustainable development acting as a moderating factor. This research aims to analyze the influence of green marketing, digital engagement, and clinic image on BPJS patient satisfaction with sustainable development as a moderating variable at Klinik Utama Sudirjo Partodimejo. The study employed a quantitative approach using purposive sampling of eligible BPJS patients. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results indicate that green marketing, digital engagement, and clinic image significantly affect patient satisfaction. Furthermore, sustainable development strengthens the influence of the independent variables on patient satisfaction. These findings suggest that the integration of environmentally friendly practices, digital service engagement, positive service image, and sustainability commitment plays an important role in enhancing patient experience and satisfaction. Keywords:Green Marketing, Digital Engagement, Clinic Image, Sustainable Development, Patient Satisfaction